The Influence of Influencer Marketing and Electronic Word of Mouth on Visiting Interest of Generation Z: A Case Study of Holywings Bar Jakarta - Maudiarti, Santi; Sembiring, Vienna Artina (Institut Pariwisata Trisakti, 2025)
The development of digital technology has brought significant changes in communication patterns and marketing strategies, particularly among Generation Z, who are highly active users of social media. In the food and beverage (F&B) industry, the use of digital-based strategies such as influencer marketing and electronic word of mouth (e-WOM) has become increasingly important for building brand image and attracting consumer interest. This study aims to examine the influence of influencer marketing and e-WOM on the visiting interest of Generation Z, using a case study of Holywings Bar Jakarta. A quantitative approach was employed by distributing questionnaires to 100 respondents belonging to the Generation Z cohort. The collected data were analyzed using validity and reliability tests, simple and multiple linear regression, as well as the coefficient of determination. The results show that influencer marketing contributes 38% to visiting interest, while e-WOM contributes 32.9%. Simultaneously, both variables account for 41% of the variation in Generation Z's interest in visiting Holywings Bar Jakarta. These findings indicate that digital marketing strategies via social media play a significant role in shaping consumer preferences and visit intentions, particularly among the younger demographic, within the context of urban entertainment destinations. Keywords: influencer marketing, electronic word of mouth, visiting interest, generation Z